About the morphology and anatomy of pollen cones and the pollen presentation within the genus Fitzroya (Cupressaceae). Issue 2 (24th February 2019) - Dörken, Veit Martin
Abstract : Fitzroya pollen cones show several features that are common for callitroid Cupressaceae including an uniaxial structure, the arrangement of microsporangiophores in trimerous whorls, and hyposporangiate microsporangiophores with several abaxial microsporangia, and a terminal scutellum. The strictly downward position of the pollen cones throughout their entire ontogeny distinguishes Fitzroya clearly from all other Cupressaceae s . str ., but is similar to some basal Cupressaceae s . l . and other coniferous groups, including several Pinaceae and Taxaceae. The peltate scutellum which covers the microsporangia is unique among Cupressaceae and all other conifers. It seems to play an important role in protecting maturing microsporangia, and also within the anemophily syndrome. In Fitzroya the pollen is not removed from the cone directly from its place of origin, but from secondary deposits located in distal parts of the scutellum. A comparable pollen exposure is lacking in all other Cupressaceae but is common in other conifers, for example several Pinaceae and Podocarpaceae. Thus, pollen cones of Fitzroya comprise features which are the common family traits of Cupressaceae, but also features that are unique among this family, but common in other conifers. In addition, also features were found that are unique among all conifers.